Analysis of the effectiveness of premedication in preventing early adverse reactions to antivenom serum from 2017 to 2021: A cohort study - Gustavo Abud Priedols; Jonas Alher Meira Alves; Jordana Meirelles de Oliveira; Jéssica Vertuan Rufino; Edmarlon Girotto; Camilo Molino Guidoni (Brazilian Journal of Pharmaceutical Sciences)
Abstract This study aimed to analyze the effectiveness of using an antivenom serum (AVS) premedication protocol to prevent early adverse reactions (EAR). This is a cohort study conducted with data from the Londrina Information and Toxicological Assistance Center (CIATox-Londrina) at the University Hospital of the State University of Londrina (HU-UEL), which included patients treated with AVS between January/2017 and December/2021. The independent variable was performing the premedication protocol and the dependent variable was the occurrence of EAR after AVS administration. Patients were followed until hospital discharge. The association analysis was performed with calculation of the Relative Risk (RR) and 95% Confidence Interval (95% CI). A total of 806 cases of accidents with venomous animals were analyzed. The minority (8.1%; n=65) had EAR, and the most frequent symptoms were related to dermatological and respiratory manifestations. The AVS premedication protocol was performed in 96.6% (n=734) of the cases. There was no statistically significant difference in the unadjusted (RR: 1.487; 95% CI: 0.530-4.174) and adjusted (RR: 1.482; 95% CI: 0.522-4.210) models regarding the performance of the AVS premedication protocol and the occurrence of EAR. It is recommended against AVS premedication given the lack of effectiveness in preventing EAR.